2011
DOI: 10.1159/000321065
|View full text |Cite
|
Sign up to set email alerts
|

Contact Sensitization in the Anal and Genital Area

Abstract: We analysed the patch test results in 1,374 patients suffering from dermatoses in the anogenital area (n = 561 genital dermatoses, n = 470 anal dermatoses, n = 343 anogenital dermatoses) patch tested in 44 dermatological departments of the Information Network of Departments of Dermatology from 2004 to 2008. All other patients patch tested during this time period without anogenital dermatoses formed the control group (n = 49, 142). Of the total study group, 662 (48.2%) patients were male. 179 (13%) had a past o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 27 publications
0
16
1
2
Order By: Relevance
“…112 A worker in a retail store had contact dermatitis which wasV unconvincinglyVascribed to beeswax a in wood varnish. 118 Other sources of sensitization to propolis include cosmetics 119 and ''biocosmetics'' or ''natural cosmetics.'' 92,114 Thus, propolis is an important allergen in patients with leg ulcers/lower-leg dermatitis, 115Y117 and the frequency of sensitization is greater than 5% in patients with anal dermatoses.…”
Section: Contact Allergy and Allergic Contact Dermatitismentioning
confidence: 99%
“…112 A worker in a retail store had contact dermatitis which wasV unconvincinglyVascribed to beeswax a in wood varnish. 118 Other sources of sensitization to propolis include cosmetics 119 and ''biocosmetics'' or ''natural cosmetics.'' 92,114 Thus, propolis is an important allergen in patients with leg ulcers/lower-leg dermatitis, 115Y117 and the frequency of sensitization is greater than 5% in patients with anal dermatoses.…”
Section: Contact Allergy and Allergic Contact Dermatitismentioning
confidence: 99%
“…Studies report various results of positive reaction to patch testing, ranging from 16% to 78%. [34][35][36][37] This wide range is explained partially by different populations tested, either patients suffering from general vulvar pruritus, specific dermatoses or highly suspected of contact dermatitis, and whether the reaction measured was relevant to the clinical presentation. It is commonly agreed, that the rate of allergic and irritant contact dermatitis among patients suffering from vulvar symptoms is high, and it is not uncommon to find it complicating other established vulvar condition.…”
Section: Patch Testsmentioning
confidence: 99%
“…This provides an ideal environment for the development of allergic contact dermatitis (ACD). Previous studies have reported rates of ACD of 29–54% in patients investigated with cutaneous allergy testing for vulval symptoms and in up to 63% in patients with anogenital symptoms …”
Section: Introductionmentioning
confidence: 98%